Make the European Green Deal real: Combining climate neutrality and economic recovery - Karlo Hainsch; Hanna Brauers; Thorsten Burandt; Leonard Göke; Christian R. von Hirschhausen; Claudia Kemfert; Mario Kendziorski; Konstantin Löffler; Pao-Yu Oei; Fabian Präger; Ben Wealer (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
The European Green Deal (EGD), a package of measures "to put Europe on a pathway to a sustainable future, while leaving no one behind", can combine climate neutrality with a sustainable economic recovery of Europe coming out of the Corona pandemic crisis. However, this requires a tightening of climate targets for 2030 already, and the development of an ambitious climate policy pathway, replacing the current "business as usual". In particular, the recovery programs must target energy efficiency and innovations for sustainable technologies, such as renewable energies, storage, and other flexibility options. This study analyzes selected areas of the European Green Deal critically, focusing on the core objective of achieving climate neutrality. The study uses energy system modeling to describe an ambitious approach to achieve climate neutrality in the spirit of the Paris climate agreement (called "Paris"- scenario) aiming for carbon neutrality by 2040. Particular focus is placed on justice and solidarity between stakeholders that are affected differently. The reference benchmark of the EGD must be climate neutrality, and coherence with the 2015 Paris climate agreement for a pathway limiting the increase of the global mean temperature to far below 2°, and if possible to 1.5°. Significant increases in energy efficiency and energy savings through behavioral change can lead to a reduction of primary energy demand by about 50% by 2050 (basis: 2015). Even under these optimistic assumptions, an increase of the greenhouse gas emission reductions ("ambition level") is necessary for 2030 and 2040, to reach climate neutrality. An appropriate target for 2030 is in the range of 60% to 65% reduction (basis: 1990), instead of the "business-as-usual", i.e. only a 40% reduction target for 2030. Despite declining final energy consumption, the trend towards electrification is increasing the demand for electricity, which is likely to more than double between 2020 (approx. 4,000 terrawatt- hours, TWh) and 2050. The declining shares of fossil and fissile power generation will be replaced mainly by onshore wind and solar photovoltaic capacities. Offshore wind plays a certain role, especially in the countries bordering the North Sea. At the end of the period, in the 2040s, 100% of supply will be secured by renewable energies. [...]
Keywords: 330; EU-Umweltpolitik; EU-Klimapolitik; Nachhaltige Entwicklung; EU-Staaten